2015
DOI: 10.5194/angeo-33-301-2015
|View full text |Cite
|
Sign up to set email alerts
|

O<sup>+</sup> transport in the dayside magnetosheath and its dependence on the IMF direction

Abstract: Abstract. Recent studies have shown that the escape of oxygen ions (O + ) into the magnetosheath along open magnetic field lines from the terrestrial cusp and mantle is significant. We present a study of how O + transport in the dayside magnetosheath depends on the interplanetary magnetic field (IMF) direction. There are clear asymmetries in the O + flows for southward and northward IMF. The asymmetries can be understood in terms of the different magnetic topologies that arise due to differences in the locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 29 publications
0
30
0
Order By: Relevance
“…The data set used for the plasma mantle statistics was obtained by SC4 andcovers 2001-2005. For the high-latitude magnetosheath we use the data set compiled by Slapak et al (2013), in which times of high-energy O + were visually determined for 2001-2003 for SC1.…”
Section: Instrumentsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data set used for the plasma mantle statistics was obtained by SC4 andcovers 2001-2005. For the high-latitude magnetosheath we use the data set compiled by Slapak et al (2013), in which times of high-energy O + were visually determined for 2001-2003 for SC1.…”
Section: Instrumentsmentioning
confidence: 99%
“…O + data in the high-latitude dayside magnetosheath covering 2001 to 2003 were identified by Slapak et al (2013) through the visual inspection of O + energy spectrograms for ion energies larger than 3 keV in order to avoid false counts due to the intense H + fluxes in the magnetosheath (Nilsson et al, 2006). The middle panel of Fig.…”
Section: The High-latitude Magnetosheathmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ion data from Cluster and Polar have revealed that a large amount of ionospheric ions are kept supplied to the exterior cusp, plasma mantle and magnetosheath, with a total flux of about 10 24−26 s −1 (Peterson et al, 2008;Slapak et al, 2013Slapak et al, , 2015 and with a local number density ratio to the solar wind of about 1 %. This amount is sufficient to substantially decelerate the solar wind by about 10 % because of 16 times heavier mass of O + than H + , and might significantly influence the electrodynamics of the polar ionosphere, e.g.…”
Section: Introductionmentioning
confidence: 99%